Bachelor Room as a Space of Hidden Homelessness: Everyday Life Performances of Turkish Immigrants in Amsterdam - Şener Kaya; Adem Sağır (İstanbul Üniversitesi Sosyoloji Dergisi)
While experiencing being foreigners in Amsterdam, Turkish immigrants staying in bachelor rooms are people who are “overshadowed” because they cannot participate in the public space outside of their own space due to certain limitations. The subject of the study is how people living in single rooms build their social relationships in the context of hidden homelessness. The study aims to understand the realities behind Turkish immigrants’ daily life experiences and performances living in bachelor rooms in Amsterdam. While studies on bachelor rooms mainly focus on issues such as housing, employment qualifications, and problems experienced by people who migrated internally, they only touch on how the people staying here build their social relations at a limited level. Additionally, bachelor pads have not been thoroughly investigated as an example of hidden homelessness. The original aspects of the study are how people who try to survive in single rooms in a different culture in Amsterdam build their social relations and the in-depth investigation of bachelor rooms in the context of hidden homelessness. While their performances in public spaces represent the front of the stage, the objective reality in this study, which tries to understand the reason for their performances in front of the stage, is that the places where people stay are one of the limited areas where they can show their true identities. A qualitative research method was preferred in the study, and in-depth interviews were conducted with convenience sampling within the scope of the explanatory case study. During the study, participants described their rooms as “tourist houses” rather than “bachelor’s houses/rooms.” The biggest problems of the individuals living here are that they come to the country illegally and do not know the language. This situation limits participation in social life and performance in daily life, which are similar to the problems experienced by people living as hidden homeless people.